If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7b+8=-7+4b
We move all terms to the left:
7b+8-(-7+4b)=0
We add all the numbers together, and all the variables
7b-(4b-7)+8=0
We get rid of parentheses
7b-4b+7+8=0
We add all the numbers together, and all the variables
3b+15=0
We move all terms containing b to the left, all other terms to the right
3b=-15
b=-15/3
b=-5
| X+2+10x=20+9x | | 3p^2-120=-9p | | 4x=6+4x | | 16(7=5b) | | m−1.47=12.15 | | 2y-10-5y=2 | | 7y-3y-7=60.48 | | 4x2+6x-4=0 | | 5y-3y-14=25.36. | | 6*x+5=81 | | 11+-11+9x=29 | | x–1=-4 | | 3x+3x-3x-2=11 | | 3x+1=4. | | 4(19=c-6) | | 2X+7(3x-5)=-16+4× | | 11=-g+10 | | 5y-3y-14=25.36 | | F(9)=5f(1) | | 11=-g | | 1/x-5=3 | | y/4+3=-18 | | 6x–1=-7 | | 3x-2/4=-7 | | y/4+4=-13 | | 3(f-1)=-4f(6) | | -11=13+6z | | 2/5+5m/3=46/15 | | x=3x-182 | | (3x/2x^2+x-3)-(2/2x+3)=4/1-x | | -12x+3=-57 | | -12x+3=57 |